MUC1 Mucin: A Putative Regulatory (Checkpoint) Molecule of T Cells - Agrawal, Babita; Gupta, Nancy; Konowalchuk, Jeffrey D. (Frontiers in Immunology, 2018)
T lymphocytes are at the center of inducing an effective adaptive immune response and maintaining homeostasis. T cell responses are initiated through cellular interactions between antigen presenting cells (APCs) and T cells. The type and strength of signals delivered through the T cell receptor (TCR) may modulate how the cells respond. The specificity of interaction is dictated by the TCR-MHC complex, whereas optimal T cell responses are dependent upon co-stimulatory signals induced by interaction of various accessory cell surface molecules. Multiple immune regulatory mechanisms brought about by coinhibitory molecules expressed on T cells play a key role in orchestrating successful and non-damaging immunity. These coinhibitory molecules are also referred to as initiators of immune check-points or co-inhibitory pathways. Knowledge of coinhibitory pathways associated with activated T lymphocytes has allowed a better understanding of a) the chronic inflammation process in infectious diseases and autoimmune diseases, and b) mechanisms by which tumors evade immune attack. Many of these regulatory pathways are non-redundant and function in a highly concerted manner. Targeting them has provided effective approaches in treating cancer and autoimmune diseases. For this reason, it is valuable to identify any co-inhibitory molecules that affect these pathways. MUC1 mucin (CD227), has long been known to be expressed by epithelial cells and overexpressed by a multitude of adenocarcinomas. As long ago as 1998 we made a surprising discovery that MUC1 is also expressed by activated human T cells and we provided the first evidence of the role of MUC1 as a novel T cell regulator. Subsequent studies from different laboratories, as well as ours, supported an immuno-regulatory role of MUC1 in infections, inflammation and autoimmunity that corroborated our original findings establishing MUC1 as a novel T cell regulatory molecule. In this article, We will discuss the experimental evidence supporting MUC1 as a putative “regulatory molecule” or a “checkpoint molecule” of T cells with implications as a novel biomarker and therapeutic target in chronic diseases such as autoimmunity, inflammation and cancer, and possibly infections.